Stereoselective Total Synthesis of (±)-Dasycarpidol and (±)-Dasycarpidone - Patir, Süleyman; Tezeren, Mustafa A.; Salih, Bekir; Ertürk, Erkan (Synthesis, 2016)
The protecting-group-free and scalable total syntheses of (±)-dasycarpidol and (±)-dasycarpidone, as well as the formal total synthesis of (±)-uleine, are presented starting from a common tetrahydrocarbazole-fused lactone that is conveniently prepared on multigram scale. The key azocino[4,3-b]indole skeleton is constructed via the DDQ-mediated dehydrogenative cyclization of a tetrahydrocarbazole derivative possessing an amide side chain. The syntheses of the target natural products are accomplished in high yields and in a few steps by employing readily available conventional reagents.
Keywords: dasycarpidone; dasycarpidol; uleine; azocino[4,3-b]indole; lactone